EVALUATING THE PERFORMANCE OF ARABIC LANGUAGE TEACHERS IN LIGHT OF SKILLFUL THINKING SKILLS - Wisal Moayad Khudair, Rasim Ahmed Abees, Hassanein Ali Diwan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Identify the skillful thinking skills of Arabic language teachers, and evaluate the performance of Arabic language teachers for the theater stage in light of the skillful thinking skills. To achieve the research objectives, the researcher followed the descriptive approach in his research procedures and the research community. (96) Teachers, and the research sample (48) teachers of Arabic language teachers in day schools, middle and high schools for boys belonging to the Karbala Holy Education Directorate, the researcher prepared a research tool, which is (the note). Form) for skillful thinking skills based on the 2008 scale of the Yolk Skilled Thinking Scale. From the validity and stability of the tool, the tool was applied, and after completing the application of the research and data analysis tool, it concluded that all areas of accurate thinking skills are acquired by Arabic language teachers, which indicates that the performance of Arabic language teachers for the preparatory stage according to skilled thinking skills in general (good)).